(untitled) (Global Journal of Science Frontier Research, 2012)
A total of ninety six day-old broiler chicks were used for this study. The birds were allotted to four dietary treatments in a completely randomized design. Each treatment had 3 replicates and there were eight birds per replicate. All birds were kept under the same managerial, environmental and hygienic conditions. The diets were formulated on isocaloric (3000.00kcal/kgME) and isonitrogenous (23.00% Crude Protein) levels. T1 (control), T2 (1g/kg yeast supplementation), T3 (1.25g/kg yeast supplementation), T4 (1.5g/kg yeast supplementation) were fed to the birds on each treatment. Data on performance (feed intake, weight gain and feed conversion ratio) and gut morphology were collected. Data were subjected to analysis of variance (ANOVA) procedure of SAS, 2010. No significant differences were observed in the weight gain of the birds in the treatments. However, birds fed T2 had the least significant feed conversion ratio (2.10kg) when compared with their counterparts on the T1 (2.34kg).